Photo-induced DNA cleavage and cytotoxicity of a ruthenium(II) arene anticancer complex - Brabec, Viktor; Pracharova, Jitka; Stepankova, Jana; Sadler, Peter J; Kasparkova, Jana (Journal of inorganic biochemistry, 2016)
We report DNA cleavage by ruthenium(II) arene anticancer complex [(η(6)-p-terp)Ru(II)(en)Cl](+) (p-terp=para-terphenyl, en=1,2-diaminoethane, complex 1) after its photoactivation by UVA and visible light, and the toxic effects of photoactivated 1 in cancer cells. It was shown in our previous work (T. Bugarcic et al., J. Med. Chem. 51 (2008) 5310-5319) that this complex exhibits promising toxic effects in several human tumor cell lines and concomitantly its DNA binding mode involves combined intercalative and monofunctional (coordination) binding modes. We demonstrate in the present work that when photoactivated by UVA or visible light, 1 efficiently photocleaves DNA, also in hypoxic media. Studies of the mechanism underlying DNA cleavage by photoactivated 1 reveal that the photocleavage reaction does not involve generation of reactive oxygen species (ROS), although contribution of singlet oxygen ((1)O2) to the DNA photocleavage process cannot be entirely excluded. Notably, the mechanism of DNA photocleavage by 1 appears to involve a direct modification of mainly those guanine residues to which 1 is coordinatively bound. As some tumors are oxygen-deficient and cytotoxic effects of photoactivated ruthenium compounds containing {Ru(η(6)-arene)}(2+) do not require the presence of oxygen, this class of ruthenium complexes may be considered potential candidate agents for improved photodynamic anticancer chemotherapy.
Keywords: Terphenyl Compounds; nádorové buněčné linie; kationty dvojmocné; organokovové sloučeniny; ethylendiaminy; Coordination Complexes; Comet assay; Light; DNA; Ruthenium anticancer complex; komplexní sloučeniny; Singlet Oxygen; světlo; ruthenium; Ruthenium; fotochemoterapie; Cell Line, Tumor; Photodynamic chemotherapy; Antineoplastic Agents; DNA cleavage; Base Sequence; sekvence nukleotidů; protinádorové látky; Ethylenediamines; Humans; Phototoxicity; Organometallic Compounds; Photochemotherapy; Plasmids; DNA Cleavage; viabilita buněk; Cell Survival; Antitumor activity; plazmidy; terfenylové sloučeniny; štěpení DNA; singletový kyslík; Cations, Divalent; lidé